Development of Generic Criteria for Evaluating the Disposability of Thermally Treated Wastes. Issue 1 (April 2020) - Harvey, L; Galson, D; Catherin, S; Romero, M-A; Fournier, M; Fuller, A; Wickham, S
Abstract: The potential to generate wasteforms with enhanced properties that support safe storage and disposal is one of the key factors driving thermal treatment of radioactive waste. Depending on the specific treatment method and waste substrate, thermal treatment can greatly reduce chemical reactivity, yielding a primary product that is more durable than wasteforms produced via non-thermal routes and with reduced potential for gas generation and other detrimental behaviour in a storage / disposal environment. On the other hand, thermal treatment can concentrate radioactivity into a smaller volume, potentially affecting waste handling and / or classification. It also generates secondary wastes whose management requires consideration as part of a holistic evaluation of thermal treatment. Moreover, some thermal treatment routes do not generate a primary product that is directly disposable without further conditioning. Generic disposability criteria have been derived that can be used to evaluate the primary products from any form of thermal treatment. These generic disposability criteria highlight the factors that are relevant for waste product disposability and the ways in which thermal treatment can impact on these factors (both positively and negatively). They are equally applicable to any packaging or disposal concept, regardless of the engineered barriers that are present, and in any disposal environment, regardless of its characteristics and the nature of the host rock / geology. They could aid waste management organisations in developing their own disposability criteria, tailored to a particular context, for application in national waste management programmes.